The evaluation of an individualised language programme in two multicultural Standard 9 classes : a pilot study - Hartman, Lorraine Mary (Rhodes University, Faculty of Education, Department of Education, 1992)
Two multicultural, mixed-ability Standard Nine classes (17 year olds) were selected for this pilot study. As they were half way through the Senior Secondary phase they had completed most of their English Language syllabus. There was a wide range of achievement in English in addition to which, fifteen of the thirty-nine pupils were English second language speakers. The teacher had to decide how to cope adequately with these differences in the subject English in general and in particular, in the Language component. A Language programme was devised, based on the prescribed textbooks. The pupils could work through the programme at their own pace and order and could consult the researcher during or after class time. The programme only covered the prescribed Language Study component and only a quarter of the total English time during an eight-week period (one term) was given to its completion. A Pre-test was set, the Senior Certificate Language examination paper of 1986, and the results analysed. The two classes were combined into one group and then randomly placed in the experimental and control groups apart from eight boys whose timetable requirements restricted them to being in the same group. The experimental and control groups were not matched. Aspects of Action Research were included in the design; pupils kept individual records; diaries were written by three pupils from each group and an independent observation was made of each group. A Post-test was administered (the 1989 Human Sciences Research Council examination) and this was followed by a questionnaire. The hypothesis, stated in null form, was: Pupils taught by individualised methods will not achieve better results than those taught by traditional methods. This hypothesis proved to be true. The experimental group, who achieved a better result in the pre-test maintained their lead over the control group but did not increase it. Neither group fared well on the post-test but the experimental group achieved a result slightly higher than the provincial average. The affective results were more positive, most pupils enjoying their autonomy and experiencing a sense of achievement despite their results in the post-test. A few preferred whole and small-group teaching, showing that the teacher needs to present the subject in more than one style. This small-scale experiment dealt only with one aspect of English teaching, but there is potential for development particularly with regard to the use of individualised programmes both for remedial and enrichment purposes. The innovative teacher in the multicultural classroom could use individualised programmes profitably as part of his teaching repertoire.
Keywords: English language -- Study and teaching (Secondary) -- South Africa; English language -- Study and teaching (Secondary) -- South Africa -- Foreign speakers; Language and education -- South Africa